Development and Effectiveness of Progressive Simulation Education Program on Medication Safety for Nursing Students. - Se-Young Jung; Eun-Young Kim (Journal of Korean Academy of Nursing, 2024)
Purpose: This study aimed to develop and verify a progressive simulation education program aimed at enhancing nursing students' medication safety competency. Methods: A non-equivalent control group pretest-posttest design was adopted. The participants were 40 third-year nursing students with no prior simulation education experience, comprising 20 each in the experimental and control groups. The experimental treatment utilized a hybrid simulation approach incorporating both full-body mannequins and standardized patients and was, conducted over three sessions with durations of 65, 80, and 95 minutes for the first, second, and third sessions, respectively, for a total of 240 minutes. The program was constructed based on Jeffries' simulation model. Results: The levels of medication safety competencies, communication self-efficacy, learning self-efficacy, and problem-solving abilities of the experimental group were significantly higher than that of the control group. Conclusion: Our results confirm that the program effectively improves nursing students' medication safety competence, communication self-efficacy, learning self-efficacy, and problem-solving ability. Therefore, this program can serve as a basis for developing educational strategies related to medication safety for nursing education institutions. Furthermore, the program is anticipated to have a positive impact on novice nurses' education and practice in clinical settings.